Latin America/Abya Yala in the World System: Geopolitics, other socio-spatial configurations and Other Horizons of Meaning: (The question of land and Earth revisited) - Carlos Walter Porto-Gonçalves (Geografares, 2023)
This article was initially intended to be published in the book organized with the interventions of the tables at the XVI Simpurb – National Symposium on Urban Geography[1] held in Vitória at the Federal University of Espírito Santo between the 14th and 17th of November 2019. As the text at the time did not have time to be revised and adapted to the book’s standards, it could not be published. We revised the article and tried to adapt some parts, but our interventions were minimal, when necessary we added an explanatory note such as Editors’ Note (EN). Part of the text sent to us by Carlos Walter was taken from an article published by him in a journal[2]. Carlos Walter’s lecture that gave rise to the text was part of Round Table 7, entitled A urban geopolitics in contemporary Latin America: disputes of the commons and whose speakers were Carlos Walter, Rodrigo Hidalgo, Mónica Arroyo and had as debater Ester Limonad[3] . Many of the references made by Carlos Walter could not be found, so the text does not always follow established citation standards. The text review was carried out by Ana Maria Leite de Barros and Cláudio Zanotelli. [1] BARROS, A.M.L.; ZANOTELLI, C.L; ALBANI, V. (ORGS.) Urban geography. 30 years of the National Symposium on Urban Geography. Cities, revolutions and injustices: between private and public spaces, the right to the city and urban commons. Rio de Janeiro: Ed. Consequência, 2020. Available at Disponible em https://simpurb2019.ufes.br/livro-do-xvi-simpurb [2] See PORTO-GONÇALVES, C. W. Of utopias and topoi: space and power in question. Geographia Opportuno Tempore, Londrina, v. 3, no. 2, p. 10-58, 2017. Available at https://doi.org/10.5433/got.2017.v3.32464. Accessed on 08-11-2023. [3]The Round Table, like all those at XVI Simpurb, was recorded and can be seen at https://youtu.be/qs_Clt2WljI?si=Q8yFsS6S1Oa3qCyF